2021
DOI: 10.1080/11101849.2021.1961428
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine-ketamine versus propofol-ketamine for sedation during upper gastrointestinal endoscopy in hepatic patients (a comparative randomized study)

Abstract: Dexmedetomidine-ketamine versus propofol-ketamine for sedation during upper gastrointestinal endoscopy in hepatic patients (a comparative randomized study), Egyptian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Seven studies ( Algharabawy et al, 2021 ; Aminnejad et al, 2022 ; Koksal et al, 2014 ; B. S. Lee et al, 2014 ; Lu et al, 2018 ; Wu et al, 2014 ; Yin et al, 2019 ) reported the RSS score of patients, with 369 patients in the control group vs. 389 patients in the DEX group. There was no significant difference between the DEX group and the control group in RSS score of patients (WMD: 0.34; 95% CI: −0.04 to 0.72; p = 0.08; I 2 = 96%) ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies ( Algharabawy et al, 2021 ; Aminnejad et al, 2022 ; Koksal et al, 2014 ; B. S. Lee et al, 2014 ; Lu et al, 2018 ; Wu et al, 2014 ; Yin et al, 2019 ) reported the RSS score of patients, with 369 patients in the control group vs. 389 patients in the DEX group. There was no significant difference between the DEX group and the control group in RSS score of patients (WMD: 0.34; 95% CI: −0.04 to 0.72; p = 0.08; I 2 = 96%) ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies ( Kilic et al, 2011 ; Takimoto et al, 2011 ; Eldesuky Ali Hassan, 2015 ; Lee et al, 2015 ; Wu et al, 2015 ; Goyal et al, 2016 ; Lu et al, 2018 ; Srivastava et al, 2018 ; Pushkarna et al, 2019 ; Yin et al, 2019 ; Algharabawy et al, 2021 ) recorded the prevalence of body movements or gagging, with 567 patients in the control group vs. 587 patients in the DEX group. The prevalence of body movements or gagging was significantly decreased in the DEX group (RR: 0.60; 95% CI: 0.37 to 0.97; p = 0.04; I 2 = 68%) compared with the control group ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dexmedetomidine decreases HR by decreasing norepinephrine levels [25]. A decrease in HR with dexmedetomidine was observed in many studies [6,7,16,21,22]. The studies by Canpolat et al and Mogahd et al showed no significance concerning changes in HR [9,26].…”
Section: Hemodynamic Parametersmentioning
confidence: 94%